Brexit and the Overseas Territories: Repercussions for the Periphery. Issue 5 (2nd September 2016) - Clegg, Peter
Abstract: There are 14 United Kingdom Overseas Territories (UKOTs), of which nine are associated with the European Union (EU) via the Overseas Association Decision adopted by the EU in 2013. Gibraltar, meanwhile, is part of the EU under Article 355(3) of the Treaty on the Functioning of the EU. Only the citizens of Gibraltar were able to vote in the referendum on the UK's membership of the EU, but the consequences for all are potentially very significant. The UKOTs benefit currently from economic and environmental cooperation, as well as development assistance and policy dialogue. The article considers briefly the growth of the relationship between the UKOTs and the EU, before setting out the key aspects of the relationship which the territories are keen to maintain. The second half of the article focuses on the (minor) role the UKOTs played in the referendum debate, and what might happen to the present levels of cooperation as the UK disengages from the EU.